2011
DOI: 10.1590/s1413-86702011000200009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of putative new Escherichia coli flagellar antigens from human origin using serology, PCR-RFlP and DNA sequencing methods

Abstract: Escherichia coli has been isolated frequently, showing flagellar antigens that are not recognized by any of the 53 antisera, provided by the most important reference center of E. coli, The International Escherichia and Klebsiella Center (WHO) of the Statens Serum Institute, Copenhagen, Denmark. The objective of this study was to characterize flagellar antigens of E. coli that express non-typeable H antigens. The methods used were serology, PCR-RFLP and DNA sequencing. This characterization was performed by gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Further, the N277 residue that reported its central role for TLR5 interaction (10) were found in H9(N277), H6, H10, H12(N276), H52(N274), H9(N277), H5, H25 (N273) and the rest serotype had substitutions in this position. The similar results were mentioned in various studies, they reported that the termini (N and C) of flagellin in E. coli are extremely conserved and vital for the flagella structure whilst the middle region can be quite variable and encodes for parts of the protein that are surface-exposed and H-type specific epitopes (20,33). The variation in length of amino acids was observed not effect on flagellin function as in H7 serotype flagellin had shorter amino acids sequence in 11 residues than H12 but didn't effect diameter of filament or its architecture.…”
Section: Detection Of Tlr5 Polymorphismssupporting
confidence: 83%
See 1 more Smart Citation
“…Further, the N277 residue that reported its central role for TLR5 interaction (10) were found in H9(N277), H6, H10, H12(N276), H52(N274), H9(N277), H5, H25 (N273) and the rest serotype had substitutions in this position. The similar results were mentioned in various studies, they reported that the termini (N and C) of flagellin in E. coli are extremely conserved and vital for the flagella structure whilst the middle region can be quite variable and encodes for parts of the protein that are surface-exposed and H-type specific epitopes (20,33). The variation in length of amino acids was observed not effect on flagellin function as in H7 serotype flagellin had shorter amino acids sequence in 11 residues than H12 but didn't effect diameter of filament or its architecture.…”
Section: Detection Of Tlr5 Polymorphismssupporting
confidence: 83%
“…The reasons why not fliC were amplified in all isolates might be due to some of H-antigen genes are at loci other than fliC such as flnaA, fllA, fmlA or flkA discovered in Salmonella species which act as alternative flagellar phase (22). It was found that 34 out of 53 H types (13, 20, and 50 not in use) in E. coli are expressed by genes at the fliC locus, with the remaining ten encoded by other loci or due to the fliC gene being at least partly deleted (33). 3).…”
Section: Detection Of Tlr5 Polymorphismsmentioning
confidence: 99%
“…Polymerase chain reaction (PCR), as a basic technology in biological and clinical research, is the most practical method of nucleic acid amplication and has been successfully applied in genetic analysis, DNA sequencing, pathogen detection, disease diagnosis, etc. [1][2][3][4][5][6] However, the traditional PCR has also shown some fundamental limitations, such as the rigorous primer design, high-precision temperature cycling, and the non-specic amplication and false-positive results, which restrict the PCR in its wide application. 7,8 It was found that the optimization of the key parameters in the PCR, including the design of primers, the annealing temperature, the number of cycles, the quality and type of the template, and the concentration of DNA polymerase, can improve the amplication efficiency and specicity.…”
Section: Introductionmentioning
confidence: 99%
“…3 Owing to its very high amplification efficiency, PCR has become one of the most popular molecular biological techniques in the past decades. 4 There have been widespread applications of PCR in many areas including gene cloning, 5 DNA sequencing, 6 genotyping, 7 genetic identity testing, [8][9][10] genetic fingerprinting, 11 forensic analysis, [12][13][14] pathogen detection 15 and disease diagnostics. 16 Despite these rapid advances, PCR technology is still faced with many challenges.…”
Section: Introductionmentioning
confidence: 99%